Clinical and radiographic evaluation of Nano-crystalline hydroxyapatite bone graft (Sybograf®) in combination with bioresorbable collagen membrane (Periocol®) in periodontal intrabony defects - Vijendra P Singh; Dilip G Nayak; Ashita S Uppoor; Dipen Shah (Wolters Kluwer Medknow Publications, 2012)
Background: Nanosized ceramics may represent a promising class of bone graft substitutes due to their improved osseointegrative properties. Nanocrystalline Hydroxyapatite (NcHA) bind to bone and stimulate bone healing by stimulation of osteoblast activity. The present study aims to explore the clinical and radiographical outcome of NcHA bonegraft (Sybograf® ) with collagen membrane (Periocol® ), in comparison with open flap debridement (OFD), in the treatment of intrabony periodontal defects. Materials and Methods: A parallel-group, randomized, controlled clinical trial was designed to conduct the study. Eighteen intrabony defects in 14 systemically healthy patients aged between 25 to 65 years were randomly assigned to test and control group. The plaque index, gingival index, probing pocket depth (PPD), clinical attachment level (CAL), and gingival recession (REC) were recorded at baseline, and were reevaluated at 6 months. In addition to this, radiographic bone fill was assessed using digital software. At the test site, NcHA bone graft and collagen membrane was placed, whereas at the control site, only OFD was done. Recall appointments were made at 7 days, 30 days, and then at 3 months and 6 months. Results: The data were subjected to statistical analysis using the Mann-Whitney 'U' Test and Wilcoxon signed rank sum test. In the control group, the mean reduction of PPD was 3.22±1.09 mm (P=0.007) and CAL gain was 2.77±1.09 mm (P=0.007). In the test group, the mean PPD reduction of 4.33±0.5 mm (P=0.006) and mean gain in CAL was 3.77±0.66 mm (P=0.006) at 6 months. The mean increase in REC was 0.55±0.72 mm (P=0.025) in test, and 0.44±0.52 mm (P=0.046) in control group. The mean gain in radiographic defect fill was 2.07±0.67 mm (P=0.008) in test and 0.91±0.21 mm (P=0.007) in control group. Conclusion: The nanocrystalline hydroxyapatite bone graft in combination with collagen membrane demonstrated clinical advantages beyond that achieved by OFD alone.